Microclimate in an agro-ecological silvopastoral system with bamboo at different tree-shade projection distances: a case study in Southern Brazil (Revista de Ciências Agroveterinárias, 2018)
The aim of the present study was to evaluate the ability of an agro-ecological silvopastoral system, composed of bamboo and tree species, to promote microclimatic alterations at different projection distances from the canopy of trees. A total of 16 paddocks in an agro-ecological silvopastoral system were evaluated. The paddocks were divided into four separate groups (silvopastoral treatments): a) Bambusa vulgaris L. and planted trees, b) only bamboo, c) only trees, and d) open grassland system. The following microclimate parameters were studied: air temperature, relative humidity, grass temperature and wind speed. All parameters were measured at a height of 20 cm above the soil. The measurements were recorded by different time intervals, in order to examine the effect of three factors: time of day, silvopasture treatment and distance to the row of trees. The results show that there was an increase in relative humidity and a reduction in wind speed close to the tree line. The agro-ecological silvopastoral system acts therefore as a windbreaker and retains humidity close to the trees. Thus, it can be concluded that regardless of the presence of bamboo, due to the limited canopy area at young stage of B. vulgaris, the agro-ecological silvopastoral system promoted microclimatic alterations to the environment, indicating the potential of this integrated system to reduce the heat load for livestock and plants.
Keywords: agroecology; biometeorology; integrated production systems; microclimate